The effect of O₂ impurities on the low-temperature radial thermal expansion of bundles of closed single-walled carbon nanotubes - Dolbin, A.V.; Esel'son, V.B.; Gavrilko, V.G.; Manzhelii, V.G.; Popov, S.N.; Vinnikov, N.A.; Sundqvist, B. (Физика низких температур, 2011)
The effect of oxygen impurities upon the radial thermal expansion αr of bundles of closed single-walled carbon nanotubes has been investigated in the temperature interval 2.2–48 K by the dilatometric method. Saturation of bundles of nanotubes with oxygen caused an increase in the positive αr-values in the whole interval of temperatures used. Also, several peaks appeared in the temperature dependence αr(T) above 20 K. The low temperature desorption of oxygen from powders consisting of bundles of single-walled nanotubes with open and closed ends has been investigated.